PENGARUH FAKTOR PERSONAL DAN LITERASI MEDIA BARU TERHADAP PERILAKU PENYEBARAN HOAX DI MEDIA SOSIAL TWITTER MENGENAI PEMBERITAAN BABI NGEPET: Survei pada Kalangan Muda di Kota Depok - Ramadhanty (2022)
This study aims to determine the influence of personal factors and new media literacy on the behavior of spreading the "Babi Ngepet" hoax on Twitter by the Depok community at the age of 18-24 years old, using the social learning theory proposed by Albert Bandura. The method used is quantitative, with the type of explanatory research. The paradigm used is the positivistic paradigm. The sampling technique used was purposive sampling. In this study, researchers used a survey technique by distributing questionnaires to 100 respondents. The analytical technique used in this research is multiple regression analysis. The results obtained in this study indicate that the contribution of age and the influence of new media literacy on positive behavior related to the spread of hoaxes is 15.9%. Meanwhile, the level of education and gender did not affect the behavior of those spreading hoaxes. The results of this study are in line with the Social Learning Theory, which states that new media literacy is a form of skill that supports the behavior. However, the results of this study do not support the theory related to the role of personal factors, including education level and gender in the behavior of those spreading hoaxes. Further research can confirm that the role of personal factors is mediated by the use of social media, it means that personal factors have an indirect influence on behavior.